Variedades afins e aplicações - Lima, Diego Ponciano de Oliveira (2013)
In this paper, we consider affine varieties in vector space to analyze and understand the geometric behavior of sets solutions of systems of linear equations, solutions of linear ordinary differential equations of second order resulting from mathematical modeling of systems, etc. We observed characteristics of affine varieties in vector spaces as a subspaces vector transferred to any vector belonging to affine variety and do a comparison of geometric representations of the solution sets of problem situations, cited above, with such features.